2019
DOI: 10.30740/j.v2i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Good Corporate Governance to the Value of Cooperative Company

Abstract: Cooperative business is directly related to the improve the business and welfare of members, so that with good supervision will have a high beneficial impact for members. Cooperative development policy should give priority to quality of cooperatives, to produces quality cooperatives required good supervision. This research was used qualitative research with description method. Implementation of Good Corporate Governance encourages cooperative management in conducting savings and loan activities effectively and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The company eventually collapsed and these was linked to unethical behaviors of board members from major corporations left many doubting the credibility of auditing as a profession and effectiveness of laid down structures that monitor and assure that corporate boards are performing according to the stakeholders' expectations (Okike, 2007). A study conducted in Indonesia by Dasuki and Lestari (2019) found that practicing good corporate governance improved earnings management and was also associated with best service delivery to the stakeholders of cooperatives in Indonesia. Another study on good corporate governance on performance of cooperatives in Nepal by Puri and Walsh (2018), the findings revealed that when effective corporate governance is in place, it leads to enhanced quality service delivery and thus benefits the cooperate members are empowered economically and socially.…”
Section: Introductionmentioning
confidence: 99%
“…The company eventually collapsed and these was linked to unethical behaviors of board members from major corporations left many doubting the credibility of auditing as a profession and effectiveness of laid down structures that monitor and assure that corporate boards are performing according to the stakeholders' expectations (Okike, 2007). A study conducted in Indonesia by Dasuki and Lestari (2019) found that practicing good corporate governance improved earnings management and was also associated with best service delivery to the stakeholders of cooperatives in Indonesia. Another study on good corporate governance on performance of cooperatives in Nepal by Puri and Walsh (2018), the findings revealed that when effective corporate governance is in place, it leads to enhanced quality service delivery and thus benefits the cooperate members are empowered economically and socially.…”
Section: Introductionmentioning
confidence: 99%
“…The Cooperative Act (2012) portends that SACCO's operations should be objective in order to advance members' economic wellbeing and their welfare in line with cooperative principles and values. Similarly Dasuki and Lestari (2019) argues that the existence of cooperatives is oriented towards members' welfare which entails accomplishing the interests of its members and the community to improve their livelihoods.…”
mentioning
confidence: 99%